Foucault and power : the influence of political engagement on the ories of power - Hoffman, Marcelo (New York : Bloomsbury, 2014)
"Michel Foucault is one of the most preeminent theorists of power, y et the relationship between his militant activities and his analysis of power remains unclear. The book explores this relationship to explain the development of Foucault's thinking about power. Using newly transla ted and unpublished materials, it examines what led Foucault to take on the question of power in the early 1970s and subsequently refine his t hinking, working through different models (war and government) and moda lities (sovereign, disciplinary, biopolitical, pastoral and governmenta l). Looking at Foucault's political trajectory, from his involvement wi th the prisoner support movement and Solidarity to his controversial en gagement with the Iranian revolution, the book shows the militant under pinning of his interest in the question of power and its various shifts and mutations. This thorough account, which includes the first transla tion of a report edited by Foucault on prison conditions, will provide students in contemporary political theory with a better understanding o f Foucault's thinking about power and of the interplay between politica l activities and theoretical productions"--
Machine generated contents note: -- Acknowledgements1. Foucault: Mil itant Analyst of Power 2. Foucault, the Prisoner Support Movement and D isciplinary Power3. Beyond the Bellicose Model of Power?4. People Versu s Population: Foucault on the Iranian Revolution 5. Foucault, Poland an d Parhessia 6. ConclusionAppendix: Investigation in 20 Prisons by the I nformation Group on PrisonsBibliographyIndex.
Includes bibliographical references (p. 205-212) and index.
Keywords: Foucault, Michel, -- 1926-1984 -- Political and social views; Foucault, Michel, -- 1926-1984 -- Influence; Power (Social sciences) -- Philosophy; Political science -- Philosophy